Composite of Cobalt‐C3N4 on TiO2 Nanorod Arrays as Co‐catalyst for Enhanced Photoelectrochemical Water Splitting. Issue 17 (5th May 2021) - Li, Yuangang; Shang, Weike; Li, Huajing; Yang, Mengru; Shi, Shaosen; Li, Jin; Huang, Chenyu; Zhou, Anning
Abstract: TiO2 @Co‐C3 N4 nanorod arrays were prepared by drop coating and hydrothermal method. The Photoelectrochemical (PEC) performance of TiO2 @Co‐C3 N4 nanorod arrays can be tuned by the amount of Co‐C3 N4 coated. When the amount of Co‐C3 N4 reached about 0.75 μg/cm 2, the PEC performance of TiO2 @Co‐C3 N4 reached the maximum. The results show that the photocurrent density of TiO2 @Co‐C3 N4 nanorod array reaches 1.79 mA/cm 2 at 1.23 VRHE, which is about 2.3 times of that from TiO2 @g ‐C3 N4 . And the PEC device has good stability and the photocurrent density remains no decline after 10 hours of continuous operation. Co atoms coordinated with g ‐C3 N4 could act as a co‐catalyst for water oxidation, and a possible mechanism is proposed for water oxidation based on careful analysis of the detailed results. The holes photogenerated by excited electrons oxidize Co atoms from Co II to Co III and Co IV, and then these high‐valence cobalt species accelerate the kinetics of water oxidation. In addition, Co‐C3 N4 not only can promote the charge transfer but also improve the overall energy conversion efficiency of the PEC device. Abstract : Composite of TiO2 @Co‐C3 N4 nanorod arrays for enhanced photoelectrochemical full water splitting with well‐retained long‐term stability.